Tyrphostin AG-related compounds attenuate H2O2-induced TRPM2-dependent and -independent cellular responses - Shinichiro Yamamoto; Takahiro Toda; Ryo Yonezawa; Takaharu Negoro; Shunichi Shimizu (Elsevier, 2017)
Purpose: TRPM2 is a Ca2+-permeable channel that is activated by H2O2. TRPM2-mediated Ca2+ signaling has been implicated in the aggravation of inflammatory diseases. Therefore, the development of TRPM2 inhibitors to prevent the aggravation of these diseases is expected. We recently reported that some Tyrphostin AG-related compounds inhibited the H2O2-induced activation of TRPM2 by scavenging the intracellular hydroxyl radical. In the present study, we examined the effects of AG-related compounds on H2O2-induced cellular responses in human monocytic U937 cells, which functionally express TRPM2. Methods: The effects of AG-related compounds on H2O2-induced changes in intracellular Ca2+ concentrations, extracellular signal-regulated kinase (ERK) activation, and CXCL8 secretion were assessed using U937 cells. Results: Ca2+ influxes via TRPM2 in response to H2O2 were blocked by AG-related compounds. AG-related compounds also inhibited the H2O2-induced activation of ERK, and subsequent secretion of CXCL8 mediated by TRPM2-dependent and -independent mechanisms. Conclusion: Our results show that AG-related compounds inhibit H2O2-induced CXCL8 secretion following ERK activation, which is mediated by TRPM2-dependent and -independent mechanisms in U937 cells. We previously reported that AG-related compounds blocked H2O2-induced TRPM2 activation by scavenging the hydroxyl radical. The inhibitory effects of AG-related compounds on TRPM2-independent responses may be due to scavenging of the hydroxyl radical.